The ANALISIS PENGARUH HUMIDITY TERHADAP LAJU KOROSI MENGGUNAKAN RIMPANG JAHE MERAH SEBAGAI PENGHAMBAT LAJU KOROSI - ayyi husbani; Novrianti Novrianti; Neneng Purnamawati (Journal of Research and Education Chemistry, 2022)
Corrosion is one the problems that occur in the production process in oil and gas industries that can reduce material equipment such as tubing and flowline. corrosion is influenced by humidity and temperature. Corrosion can be control by using organic inhibitors because they are environmentally friendly. This research is a laboratory research that examines the effect of humidity using red ginger on reducing corrosion flow rate. Red ginger is used because it contains phenol antioxidants which can inhibit the corrosion flow rate. The variables used were variations in room humidity, 80%, and 90% and the inhibition time was 72 hours, 144 hours, and 216 hours. The results showed that the sample by adding red ginger inhibitor at room temperature humidity, 80%, 90% was able to maximize decrease in the corrosion rate. The sample with the addition of ginger inhibitor showed the higher the humidity value, the higher the corrosion rate where the highest corrosion rate was 0.1362 mmpy at 90% humidity, while the lowest humidity was obtained at room humidity of 0.0517 mmpy. Keywords : Humidity, Corrosion, Inhibitor, Red ginger, Coating